Blood vessels as regulators of neural stem cell properties - Karakatsani, Andromachi; Shah, Bhavin Shailesh; Ruiz de Almodóvar, Carmen (Frontiers in molecular neuroscience, 2019)
In the central nervous system (CNS), a precise communication between the vascular and neural compartments is essential for proper development and function. Recent studies demonstrate that certain neuronal populations secrete various molecular cues to regulate blood vessel growth and patterning in the spinal cord and brain during development. Interestingly, the vasculature is now emerging as a critical component that regulates stem cell niches during neocortical development, as well as during adulthood. In this review article, we will first provide an overview of blood vessel development and maintenance in embryonic and adult neurogenic niches. We will also summarize the current understanding of how blood vessel-derived signals influence the behavior of neural stem cells (NSCs) during early development as well as in adulthood, with a focus on their metabolism.